France : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
This 2014 Article IV Consultation highlights that the economy of France fared better than most other large euro areas economies through the crisis, reflecting the resilience of private consumption, lack of financial fragmentation, and lower levels of household and corporate debt. Banks' financial position has also been strengthened. But after two years of near stagnation, unemployment remains high. A loss of competitiveness has also weighed on growth. The outlook is for a gradual recovery, with GDP growth projected at 0.7 percent in 2014 and 1.4 percent in 2015, based on stronger external and domestic private demand, reflecting gains in real disposable income and improved profit margins.